Investigating the Aspects of Educating Students in Technical Universities - Karpanina, E.N. (2020)
The article discusses the practical aspects of pedagogy that contribute to the success of the formation of civic education of students in the educational space of a technical university. The problems of the formation of civic education of students and the scientific coordination of the educational process in modern higher education are analyzed.